Anal fistula metastasis of rectal cancer after neoadjuvant therapy: a case report - Shota Fukai; Shingo Tsujinaka; Yasuyuki Miyakura; Natsumi Matsuzawa; Yuuri Hatsuzawa; Ryo Maemoto; Nao Kakizawa; Toshiki Rikiyama (Surgical Case Reports)
Abstract Background Anal metastasis of colorectal cancer is very rare and may present synchronously or metachronously, regardless of pre-existing anal diseases. We report a case of anal fistula metastasis after completion of neoadjuvant therapy for rectal cancer, followed by surgical resection of the primary tumor and metastatic lesion. Case presentation A 50-year-old man was diagnosed with rectal cancer located 5 cm from the anal verge, with a clinical stage of cT3N0M0. He denied any medical or surgical history, and physical examination revealed no perianal disease. He underwent preoperative chemoradiation therapy (CRT) consisting of a tegafur/gimeracil/oteracil potassium (S-1)-based regimen with 45 Gy of radiation. After completion of CRT, computed tomography (CT) revealed the primary tumor’s partial response, but a liver mass highly suggestive of metastasis was detected. This mass was later diagnosed as cavernous hemangioma 3 months after CRT initiation. He then underwent and completed six cycles of consolidation chemotherapy with a capecitabine-based regimen. Subsequent colonoscopy revealed the complete response of the primary tumor, but CT showed thickening of the edematous rectal wall. Therefore, we planned to perform low anterior resection as a radical surgery. However, he presented with persistent anal pain after the last chemotherapy, and magnetic resonance imaging revealed a high-intensity mass behind the anus, suggestive of an anal fistula. We considered the differential diagnosis of a benign anal fistula or implantation metastasis into the anal fistula. Fistulectomy was performed, and a pathological diagnosis of tubular adenocarcinoma, suggestive of implantation metastasis, was made. Thereafter, we performed laparoscopic abdominoperineal resection. Histopathological examination revealed well-differentiated adenocarcinoma, ypT2N0, with a grade 2 therapeutic effect. Subsequent immunohistochemistry of the resected anal fistula showed a CDX-2-positive, CK20-positive, CK7-negative, and GCDFP-15 negative tumor, with implantation metastasis. There was no cancer recurrence 21 months after the radical surgery. Conclusions This is the first report of anal fistula metastasis after neoadjuvant therapy for rectal cancer in a patient without a previous history of anal disease. If an anal fistula is suspected during or after neoadjuvant therapy, physical and radiological assessment, differential diagnosis, and surgical intervention timing for fistula must be carefully discussed.